Nazhariyah Noam Chomsky fii An-Numu Al-Lughawi wa In’ikasatuha ‘ala Ta’lim Al-Lughah Al-Arabiyah - Ningsih, Anita Andriya; Munir, Muhammad Mubasysyir; Mustapa, Mustapa (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
Chomsky argues that the language is too complicated to learn through passages, such as studying city rosters around the world. Since the early 1970s, theoretical disciplines and teaching methodologies have continuously sought to realize their symbiotic relationships. Teaching language within the framework of Chomsky's theory should give students an appropriate linguistic description with due regard to the student's intellectual level. Language is not only a device for capturing information from what it has learned, but in fact it returns to the student's mental and cognitive ability to complete the process. ÙŠØ±Ù‰ ØªØ´ÙˆÙ…Ø³ÙƒÙŠ Ø¨Ø£Ù† Ø§Ù„Ù„ØºØ© Ù…Ø¹Ù‚Ø¯Ø© Ù„Ù„ØºØ§ÙŠØ© Ø¨ØÙŠØ« Ù„Ø§ ÙŠÙ…ÙƒÙ† ØªØ¹Ù„Ù…Ù‡Ø§ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ù…Ù‚Ø§Ø·Ø¹ ØŒ Ù…Ø«Ù„ Ø¯Ø±Ø§Ø³Ø© Ù‚ÙˆØ§Ø¦Ù… Ø§Ù„Ù…Ø¯Ù† ØÙˆÙ„ Ø§Ù„Ø¹Ø§Ù„Ù…. Ù…Ù†Ø° Ø£ÙˆØ§Ø¦Ù„ Ø§Ù„Ø³Ø¨Ø¹ÙŠÙ†ÙŠØ§Øª ØŒ Ø³Ø¹Øª Ø§Ù„ØªØ®ØµØµØ§Øª Ø§Ù„Ù†Ø¸Ø±ÙŠØ© ÙˆÙ…Ù†Ù‡Ø¬ÙŠØ§Øª Ø§Ù„ØªØ¯Ø±ÙŠØ³ Ø¨Ø§Ø³ØªÙ…Ø±Ø§Ø± Ø¥Ù„Ù‰ Ø¥Ø¯Ø±Ø§Ùƒ Ø¹Ù„Ø§Ù‚Ø§ØªÙ‡Ø§ Ø§Ù„ØªÙƒØ§ÙÙ„ÙŠØ©. ÙŠØ¬Ø¨ Ø£Ù† ØªØ¹Ø·ÙŠ Ù„ØºØ© Ø§Ù„ØªØ¯Ø±ÙŠØ³ ÙÙŠ Ø¥Ø·Ø§Ø± Ù†Ø¸Ø±ÙŠØ© ØªØ´ÙˆÙ…Ø³ÙƒÙŠ Ù„Ù„Ø·Ù„Ø§Ø¨ ÙˆØµÙÙ‹Ø§ Ù„ØºÙˆÙŠÙ‹Ø§ Ù…Ù†Ø§Ø³Ø¨Ù‹Ø§ Ù…Ø¹ Ø¥ÙŠÙ„Ø§Ø¡ Ø§Ù„Ø§Ø¹ØªØ¨Ø§Ø± Ø§Ù„ÙˆØ§Ø¬Ø¨ Ù„Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„ÙÙƒØ±ÙŠ Ù„Ù„Ø·Ø§Ù„Ø¨. Ø§Ù„Ù„ØºØ© Ù„ÙŠØ³Øª ÙÙ‚Ø· Ø£Ø¯Ø§Ø© Ù„Ø§Ù„ØªÙ‚Ø§Ø· Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ù…Ù…Ø§ ØªØ¹Ù„Ù…ÙˆÙ‡ ØŒ ÙˆÙ„ÙƒÙ†Ù‡Ø§ ÙÙŠ Ø§Ù„ÙˆØ§Ù‚Ø¹ ØªØ¹ÙˆØ¯ Ø¥Ù„Ù‰ Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ø§Ù„Ø¨ Ø§Ù„Ø¹Ù‚Ù„ÙŠØ© ÙˆØ§Ù„Ù…Ø¹Ø±ÙÙŠØ© Ù„Ø¥ÙƒÙ…Ø§Ù„ Ø§Ù„Ø¹Ù…Ù„ÙŠØ©.